Cardiac magnetic resonance derived global longitudinal strain outperforms established functional parameters in prognostication after ST-elevation myocardial infarction. (8th February 2021) - Holzknecht, M; Reindl, M; Tiller, C; Lechner, I; Hornung, T; Plappert, D; Klug, G; Reinstadler, SJ; Bauer, A; Metzler, B; Mayr, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although left ventricular ejection fraction (LVEF) is recommended for left ventricular (LV) systolic function assessment and risk stratification of patients with ST-elevation myocardial infarction (STEMI), its prognostic value is limited. Other measures of LV function such as global longitudinal strain (GLS) and mitral annular plane systolic excursion (MAPSE) might provide additional prognostic information post-STEMI. However, comprehensive investigations comparing these parameters in terms of prediction of hard clinical events following STEMI are lacking so far. Purpose: We aimed to investigate the comparative prognostic value of LVEF, MAPSE and GLS by cardiac magnetic resonance (CMR) imaging in acute STEMI patients. Methods: This observational study included 407 consecutive acute STEMI patients treated with primary percutaneous coronary intervention (PCI). Comprehensive CMR investigations were performed 3 [interquartile range (IQR): 2-4] days after PCI to determine LVEF, GLS and MAPSE as well as myocardial infarct characteristics. Primary endpoint was the occurrence of MACE defined as composite of death, re-infarction and congestive heart failure. Results: During a follow-up of 21 [IQR: 12-50] months, 40 (10%) patients experienced MACE. Patients with MACE showed significantly lower LVEF (49% vs. 53%, p = 0.005) and MAPSE (7.9 mm vs. 9.1 mm, p = 0.001), as well as higher GLS values (-10.2% vs. -12.3 %, p < 0.001). GLS showed the highest prognostic value with an area under the curve (AUC) of 0.71 (95% CI 0.63-0.79; p < 0.001) compared to MAPSE (AUC: 0.67, 95% CI 0.58-0.75; p = 0.001) and LVEF (AUC: 0.64, 95% CI 0.54-0.73; p = 0.005). After multivariable analysis, GLS emerged as independent predictor of MACE (HR: 1.22, 95% CI 1.11-1.35; p < 0.001). Of note, GLS remained associated with MACE (p < 0.001) even after adjustment for infarct size and microvascular obstruction. Conclusion: CMR-derived GLS emerged as strong and independent predictor of MACE after acute STEMI with additive prognostic validity to LVEF and parameters of myocardial damage.